Investigation of stability and reliability of the patient's wireless temperature monitoring device - Imran Gulcharan, N.F.B. (Elsevier B.V., 2014)
Currently, wireless radio frequency (RF) communication and Wireless Sensor Network (WSN) has shifted its trend on human or item tracking capability to real time monitoring capability especially in healthcare industry. Monitoring patient's condition is one of the crucial tasks in any hospital to ensure patients are in good and stable condition. Efforts have been made by many researchers to use WSN to measure temperature, heart rate, oxygen saturation, respiratory rate and etc. to monitor patient's condition remotely in hospitals. This research focuses on integrating a temperature sensor to a wireless transceiver Zigbee network and is used to measure patient's body temperature from remote location (nurse's workstation. Few thermistor temperature sensors were used to determine reliability and their reading were compared against thermometer and the one with an accurate and stable reading was chosen. Zigbee network or accurately known as IEEE 802.15.4/Zigbee is known to be a low power consumption device with better transmission range higher network flexibility and large number of nodes. Through the experimentation Zigbee network is proven capable to provide stability in data transmission at longer range at different temperature environment. Â© 2014 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license.